The irruption of private interest in education in Costa Rica, in relation to the programs of Civic Education - Agüero García, Javier (2016)
This essay analyzes the Costa Rican government action towards education. This action has been embodied by the Ministry of Public Education in its educational policy, in regards to the elaboration of the national Civic Education syllabus for General Basic Education (Third Cycle: composed by seventh, eighth and ninth grades). The analysis shows that the educational policy, with regard to the elaboration of curricula of civic, has been characterized by the intrusion of private enterprise in the preparation of aimed content for public education; this issue is immersed in a context of neoliberalism which flies the flag of minimizing the role of the State. Thus, the hegemonic group is formed by the sector which manages the MEP (Ministry of Public Education), with the interests of third parties, in this case from private companies. This group exerts social control by teaching certain values to students through the implementation of these syllabuses, which were approved in 2008 and implemented in 2009.